Efficacy of Acupuncture for Treatment of Atopic Eczema and Chronic Eczema: A Systematic Review and Meta-analysis - Jhen-Yu Jwo; Katie Chiou; Jerry Tsai; Yu-Chen Huang; Chia-Yu Lin (Medical Journals Sweden, 2022)
Abstract is missing (Short communication)